2016
DOI: 10.7249/rr844
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Treatment of Mild Traumatic Brain Injury in the Military Health System

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 61 publications
(108 reference statements)
0
26
0
Order By: Relevance
“…Our findings demonstrated that occupational risk for LLB may be associated with greater susceptibility to concussion and moderate TBIs, but not severe or penetrating TBIs, which are likely caused by sufficiently forceful events or impacts to the head to result in TBI regardless of occupational exposure to LLB. Interestingly, the effect of occupational risk for LLB exerted a stronger effect on moderate TBIs compared with concussions, which may be partially explained by the fact that people often do not seek medical care for a concussion, thus such effects would not be observed in studies using healthcare reimbursement records [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings demonstrated that occupational risk for LLB may be associated with greater susceptibility to concussion and moderate TBIs, but not severe or penetrating TBIs, which are likely caused by sufficiently forceful events or impacts to the head to result in TBI regardless of occupational exposure to LLB. Interestingly, the effect of occupational risk for LLB exerted a stronger effect on moderate TBIs compared with concussions, which may be partially explained by the fact that people often do not seek medical care for a concussion, thus such effects would not be observed in studies using healthcare reimbursement records [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was possible for each service member to have been diagnosed with more than one type of TBI during the study period. Furthermore, given the direct focus on concussion in the present research, additional relevant conditions were recorded using case criteria established in a recent RAND report on concussion [ 32 ]. Diagnoses commonly comorbid with concussion that were identified for analysis included alteration in mental status, cognitive problems, communication disorders, dizziness/vertigo, gait and coordination problems, headache, hearing problems, non-headache pain, skin sensation disturbances, sleep disorders/symptoms, smell and taste disturbances, syncope/collapse, and vision problems.…”
Section: Methodsmentioning
confidence: 99%
“…Military personnel are particularly at risk for TBI. Lack of access to safe and accessible transportation for deployed military personnel can delay treatment up to 72 h after TBI (Farmer et al, 2017). Thus, treatment gap likely contributes to negative outcomes after TBI.…”
Section: Therapeutic Time Window Is a Key Element Of Drugs To Treat Tbimentioning
confidence: 99%
“…In these cases, generally no emergency intervention is required. Mild TBI will be the focus of this review, as mTBIs account for 84% of military brain injuries [12] and have more recently been recognized as an important clinical entity. It should be noted that the definitions described below are not universally utilized, and differences in the definition of TBI severity across studies likely contribute to differences in conclusions.…”
Section: Considerations For the Study Of Military Tbimentioning
confidence: 99%